Stillbirth trends by maternal sociodemographic characteristics among a large internal migrant population in Shenzhen, China, over a 10-year period: a retrospective study - Rui Ma; Lingyun Zou (BMC, 2022)
Abstract Background Cities such as Shenzhen in southern China have large immigrant populations, and the reproductive health issues of pregnant women in these populations have not received sufficient attention. Stillbirth seriously threatens their health and is becoming a social issue worthy of attention. We conducted this study to estimate the trend in stillbirths at 28 or more gestational weeks and the related sociodemographic characteristics of pregnant women among a large internal migrant population in South China. Methods A stillbirth is defined as a baby born with no signs of life after a given threshold, and are restricted to births of 28 weeks of gestation or longer, with a birth weight of at least 1000 g for international comparison. A population-based retrospective cohort of all births from January 2010 to December 2019 in Baoan, Shenzhen, was conducted using the Shenzhen Birth Registry Database. The overall stillbirth rate and year-specific stillbirth rate were calculated as the number of foetal deaths ≥28 gestational weeks or a birth weight ≥ 1000 g divided by the number of births over the last decade or in each year, respectively. The associations between the risk of stillbirth and maternal sociodemographic status were assessed using logistic regression. Spearman's rank correlation was calculated to evaluate the correlation between the economic status of the maternal birthplace and the stillbirth. Results An overall stillbirth rate of 4.5 per 1000 births was estimated in a total of 492,184 births in our final analysis. Migrant women accounted for 87% of the total population but had a higher stillbirth rate (4.8 per 1000 births) than the permanent population (2.8 per 1000 births). The stillbirth rate varied by region of maternal birthplace, from 4.1 per 1000 births in women from East China to 5.7 per 1000 births in women from West China. The GDP per capita of the maternal birthplace was strongly correlated with the stillbirth rate. Conclusions Large disparities in the stillbirth rate exist between migrant and permanent populations and among regions of maternal birthplace in China. Strategies targeting migrant women based on their maternal birthplace are needed to further reduce the burden of stillbirth.